The politics of the street: Street art, public writing and the history of political contest in Chile. (1st June 2021) - Trumper, Camilo
Abstract : This commentary focuses on the politics of public space in democracy and dictatorship. It delves into what Peter Winn calls the revolution 'from below' from the perspective of urban conflict, suggesting a political history that attends to urban and visual culture as a crucial arena of political practice . It suggests that the often-conflictive battle over public spaces was, and continues to be, a mechanism by which an unprecedented range of citizens entered into an ongoing debate over the boundaries of citizenship, practice, politics and that this practice was adapted, transformed and reimagined over the last five decades. The struggle over streets and walls continues to be central to Chilean political history, and urban space remains a field of ongoing contest and debate: the estallido of social unrest in contemporary Chile connected a new generation of activists to this longer history of creative politics of protest and protest art and gave them the opportunity to articulate new forms of intersectional political thought in public space, even in the face of state-sponsored violence. Studying these forms of unrest reveals that theirs is an incisive, intersectional critique of the limits of the 'transition to democracy', of neoliberal democracies and of the legacies of dictatorship.